ELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND NUTRITIONAL STATUS - Widi Nurwijayanti (Journal of Holistic and Traditional Medicine, 2021)
Indonesia is a developing country that is experiencing multiple nutritional problems. The dual nutritional problem currently facingIndonesia is the occurrence of malnutrition problems that have not been resolved and at the same time, there is a problem of overnutrition. The habits of today's society tend to be passive or known with a sedentary life pattern. This is due to a lack of physicalactivity undertaken so that a person's nutritional status can change. Along with changes in the nutritional status of the communitydue to lack of physical activity performed. This can then be assessed by one of them using anthropometric measurements of BodyMass Index (BMI).